The Role of the Partnership and Community Development Program in Increasing Firm Value - Andini Melinia Sari (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this study was to examine the effect of the effectiveness of the Partnership and Community Development Program (PKBL) in increasing firm value mediated by financial performance. The population of this research is State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange. In determining the sample, purposive sampling technique was used which resulted in 7 companies with 35 observation data as samples in this study. The method used is quantitative with secondary data sources using documentation as a data collection technique. The data analysis technique in this study uses panel data regression processed with e-views software. The results found that the effectiveness of the Partnership and Community Development Program (PKBL) and financial performance had a positive effect on firm value, but the effectiveness of the Partnership and Community Development Program (PKBL) had no effect on financial performance. Furthermore, financial performance is able to mediate the relationship between the effectiveness of the Partnership and Community Development Program (PKBL) on firm value, so that financial performance can be stated as partial mediation.